Co–Doped Fe–Co@C–Nx Nano-Arrays Grown on Carbon Cloth as a Novel Flexible Electrode for In Situ Detection of Extracellular Hydrogen Peroxide. Issue 8 (4th August 2021) - Zhou, Shiying; Zhao, Peng; Zheng, Jilin; Chen, Sha; Yang, Mei; Huo, Danqun; Hou, Changjun
Abstract : Flexible electrodes play an increasingly important role in the development of portable and wearable electronics. Herein, a novel flexible and self-supporting electrode supported on active electrocatalyst (Au/Fe–Co@C–Nx/GO/CC) has been prepared for in situ detection of extracellular H2 O2 . The Fe, N co-doping of Fe–Co@C–Nx with abundant active sites promotes electron transfer efficiency, and Fe–Co@C–Nx nano-arrays with a unique spatial structure are beneficial for the deposition of Au nanoparticles (AuNPs). Graphene oxide (GO) serves as a chemical bridge to ensure that the nanomaterials grow more uniformly and firmly on the carbon cloth. Meanwhile, the flexible carbon cloth possesses stable mechanical and electrochemical properties. Based on these unique superiorities, this flexible electrode exhibits excellent sensing performance toward H2 O2 with high selectivity and sensitivity, low LOD (0.56 μ M), and wide linear range (from 5 to 21195 μ M). Most importantly, the prepared electrode can adhere to cells for in situ and sensitive determination of H2 O2 released from cells. Compared to detecting H2 O2 in cell suspensions, in situ detection can capture the signal molecules more sensitively and effectively, avoiding the diffusion of H2 O2 from the solution to the electrode surface. This flexible electrode has great potential in development of molecular detection and portable electronics.